PERAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER SISWA DI MTS SWASTA MADINATUSSALAM - Muhammad Yunanda Yano Putra; Nurman Ginting (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of this research is to explain the role of religious education in helping the process of character formation of students at Madinatussalam Private MTs. Qualitative descriptive research method. In the process of collecting data, using observation, interviews and documentation methods. Meanwhile, for the analysis, qualitative descriptive analysis techniques are used, namely in the form of written or verbal data from people and observed behavior so that in this case the author attempts to conduct research that thoroughly describes the actual situation. The author can conclude the results of this research as follows: First, the school's efforts to realize character education are: 1) conducting Islamic studies,2) take advantage of the commemoration of Islamic Holidays (PHBI); 3) oblige and get used to saying hello and shaking hands with teachers Second, the efforts of Islamic religious education teachers in forming student character: 1) maximizing the delivery of Islamic religious education material; 2) instilling the Islamic style of Ahlusunnah Waljama'ah; 3) Islamic religious education teachers must be active and be role models for their students in applying character education. Third, the strategies carried out by Islamic religious education teachers: 1) use of effective learning approach methods; 2) use of discussion and demonstration methods